2022
DOI: 10.1021/acs.iecr.2c02216
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of RuCo/MgTiO3 Catalysts for Nonthermal Plasma-Assisted Ammonia Synthesis

Abstract: The development of robust yet effective catalysts is vital for promoting nonthermal plasma (NTP)-assisted ammonia (NH 3 ) synthesis toward practical applications. Herein, we report a simple mechanochemical synthesis method (via ball milling) for preparing bimetallic RuCo supported on MgTiO 3 catalyst (i.e., RuCo/MgTiO 3 -6-500) to be used in NTP-assisted catalytic NH 3 synthesis. The physicochemical properties of the developed catalysts were investigated systematically with respect to the relevant process para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…In contrast, the synthesis rate is remarkably increased to 64.42 and 60.11 μmol/(min·g cat ), respectively, using AsVPd-SBA15 and SiVPd-SBA15 as catalysts. Such performances are far better than most of the catalysts reported previously (see Table S3) as well as the referenced Al 2 O 3 (29.34 μmol/(min·g cat )) and SBA-15 (39.85 μmol/(min·g cat )). , Meanwhile, V 10 -SBA15 (5 wt % V) and Pd/C (5 wt % Pd) were examined as a control, and the synthesis rate is 44.44 and 21.94 μmol/(min·g cat ), respectively, suggesting the combination advantage of Pd and SBA-15 in our catalysts. Also, the synthesis rate of the vanadate-free Pd 13 As 8 -SBA15 (1.5 wt % Pd) is 56.26 μmol/(min·g cat ), indicating the positive role of vanadates in promoting the catalytic efficiency.…”
Section: Resultsmentioning
confidence: 76%
“…In contrast, the synthesis rate is remarkably increased to 64.42 and 60.11 μmol/(min·g cat ), respectively, using AsVPd-SBA15 and SiVPd-SBA15 as catalysts. Such performances are far better than most of the catalysts reported previously (see Table S3) as well as the referenced Al 2 O 3 (29.34 μmol/(min·g cat )) and SBA-15 (39.85 μmol/(min·g cat )). , Meanwhile, V 10 -SBA15 (5 wt % V) and Pd/C (5 wt % Pd) were examined as a control, and the synthesis rate is 44.44 and 21.94 μmol/(min·g cat ), respectively, suggesting the combination advantage of Pd and SBA-15 in our catalysts. Also, the synthesis rate of the vanadate-free Pd 13 As 8 -SBA15 (1.5 wt % Pd) is 56.26 μmol/(min·g cat ), indicating the positive role of vanadates in promoting the catalytic efficiency.…”
Section: Resultsmentioning
confidence: 76%
“…The use of nonthermal plasma technology to synthesize NH 3 has been studied extensively. Compared with traditional synthetic NH 3 technology, synthesizing NH 3 with plasma technology has the advantages of mild reaction conditions and no greenhouse gas emissions . It has been reported that H 2 and N 2 can synthesize NH 3 under the combined action of plasma and catalyst, and catalyst research is the focus.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional synthetic NH 3 technology, synthesizing NH 3 with plasma technology has the advantages of mild reaction conditions and no greenhouse gas emissions. 17 Mizushima et al 18 used a tubular membrane-like catalyst for a reactor with dielectric barrier discharge (DBD) plasma in NH 3 synthesis. 18,19 The results show that the catalysts can effectively increase the yield of NH 3 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Non-thermal plasma (NTP) is a promising alternative to enable many challenging and important chemical reactions (particularly limited by kinetics and/or thermodynamics), such as CO 2 hydrogenation, [1][2][3][4][5][6] water gas shift (WGS) reaction, [7][8][9] and ammonia synthesis. [10][11][12][13] Unlike thermal methods, NTP can be generated under relatively mild conditions (e.g. ambient temperature and pressure) without external heat sources, offering a number of advantages such as achieving steadystate quickly and switching on/off easily, making it promising to use the intermittent electricity (generated from abundant renewable sources such as wind and solar) for distributed production.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐thermal plasma (NTP) is a promising alternative to enable many challenging and important chemical reactions (particularly limited by kinetics and/or thermodynamics), such as CO 2 hydrogenation, 1–6 water gas shift (WGS) reaction, 7–9 and ammonia synthesis 10–13 . Unlike thermal methods, NTP can be generated under relatively mild conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%